Important Study about the Lost and Found World of Litvaks - Stasiulis, Stanislovas (Lietuvos istorijos studijos, 2015)
Rec.: Šarūnas Liekis, Antony Polonsky, Chaeran Freeze (eds.), Polin: Studies in Polish Jewry: Jews in the Former Grand Duchy of Lithuania since 1772, Oxford: The Littman Library of Jewish Civilization, 2013, 509 p.